BISMICS consensus statement: implementing a safe minimally invasive mitral programme in the UK healthcare setting. Issue 2 (5th October 2020) - Vohra, Hunaid A; Salmasi, M Yousuf; Chien, Lueh; Baghai, Max; Deshpande, Ranjit; Akowuah, Enoch; Ahmed, Ishtiaq; Tolan, Michael; Bahrami, Toufan; Hunter, Steven; Zacharias, Joseph
Abstract : Disseminating the practice of minimally invasive mitral surgery (mini-MVS) can be challenging, despite its original case reports a few decades ago. The penetration of this technology into clinical practice has been limited to centres of excellence, and mitral surgery in most general cardiothoracic centres remains to be conducted via sternotomy access as a first line. The process for the uptake of mini-MVS requires clearer guidance and standardisation for the processes involved in its implementation. In this statement, a consensus agreement is outlined that describes the benefits of mini-MVS, including reduced postoperative bleeding, reduced wound infection, enhanced recovery and patient satisfaction. Technical considerations require specific attention and can be introduced through simulation and/or use in conventional cases. Either endoballoon or aortic cross clamping is recommended, as well as femoral or central aortic cannulation, with the use of appropriate adjuncts and instruments. A coordinated team-based approach that encourages ownership of the programme by the team members is critical. A designated proctor is also recommended. The organisation of structured training and simulation, as well as planning the initial cases, is an important step to consider. The importance of pre-empting complications and dealing with adverse events is described, including re-exploration, conversion to sternotomy, unilateral pulmonary oedema and phrenic nerve injury. Accounting for both institutional and team considerations can effectively facilitate the introduction of a mini-MVS service. This involves simulation, team-based training, visits to specialist centres and involvement of a designated proctor to oversee the initial cases.